2017
DOI: 10.1177/0333102417748928
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of glucose metabolism and the role of NPY in the progression of insulin resistance in chronic migraine

Abstract: Background Chronic migraine has a well-documented association with increased insulin resistance and metabolic syndrome. The hypothalamus may play a role in the progression of insulin resistance in chronic migraine through the regulation of orexigenic peptides such as neuropeptide Y. Insulin resistance may lead to increased risk of future type 2 diabetes mellitus in patients with chronic migraine, which is more likely to occur if other pathogenetic defects of type 2 diabetes mellitus, such as impaired pancreati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 50 publications
3
24
0
Order By: Relevance
“…This might also be the case for plasma and serum, for example, we observed a significant increase in the NPY serum level but a significant decrease in the NPY plasma level in migraine patients compared with CTRL (Table 3). 38,88,89 Complete metabolomic profiling of primary headache patients and use of the serum metabolome database might reveal useful knowledge in the discussion of unique subgroup profiles, for example, defined by multiple strata 90 . In the future, investigation of plasma, serum, and whole blood in the same study might aid in the understanding of differential signaling molecule profiles in primary headache patients.…”
Section: Discussionmentioning
confidence: 99%
“…This might also be the case for plasma and serum, for example, we observed a significant increase in the NPY serum level but a significant decrease in the NPY plasma level in migraine patients compared with CTRL (Table 3). 38,88,89 Complete metabolomic profiling of primary headache patients and use of the serum metabolome database might reveal useful knowledge in the discussion of unique subgroup profiles, for example, defined by multiple strata 90 . In the future, investigation of plasma, serum, and whole blood in the same study might aid in the understanding of differential signaling molecule profiles in primary headache patients.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have provided evidence for an associa tion between migraine and insulin resistance (reviewed elsewhere 84 ), although this association was not seen at all in one study 85 and only in women with migraine in another 86 . One study has shown that β cell function, and therefore insulin production, is normal in patients with migraine but that the degree of insulin resistance correlates with disease severity 87 .…”
Section: Oxidative and Nitrosative Stress And Antioxidant Capacitymentioning
confidence: 99%
“…Evolving work in rheumatology and chronic pain has recognized IR in many pain conditions, including migraine, neuropathic pain, and multiple other conditions leading to chronic pain (9)(10)(11)(12)(13). Also, IR is associated with dementia in patients with Parkinson's disease and cognitive impairment with fibromyalgia (FM) (14,15).…”
mentioning
confidence: 99%